FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI KOTA BENGKULU - Hermansyah, Hermansyah (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Data of Bengkulu City Health Department show that in the last 5 years the number of dengue cases in the city of Bengkulu continues to increase. This study aims to determine the factors associated with the incidence of dengue hemorrhagic fever in the city of Bengkulu in 2012. The type of research used was the analytic case-control design. The populations in this study were all citizens of Bengkulu town. The total number of sample was 37 people for groups of cases and 37 people for the control group. The samples were taken by consecutive sampling technique. The data were collected with interview techniques and direct observation by using questionnaires. The data analysis was performed with univariate and bivariate analysis with Chi-Square test at α 5%. The results showed that more than half of respondents (54.1%) in the case and a minority of respondents (27%) in the control group had lack knowledge level about the prevention of dengue disease, the majority of respondents (80.1%) in the case and more than half of respondents (56.8%) in the control group had a lack habit of implementing 3M's, more than half of respondents (67.6%) and a minority of respondents (37.8%) in the control group, it was found that they did not have quite fine environment. There was a significant association between knowledge about dengue prevention (p = 0.033), the habit of carrying out the movement of 3M (p = 0.044,) and the condition of the home environment (p = 0.02) with the incidence of dengue in the city of Bengkulu in 2012. It is recommended to the Bengkulu City Health Department and health centers to further intensify do health promotion activities on dengue prevention in order to increase knowledge and awareness to maintain a healthy home environment, especially with the motion mosquito eradication nest (PSN).